Consistent Design of Relational Databases using EERCASE - N. Fidalgo, Robson; A. Silva, Edson (Journal of Information and Data Management, 2022)
This article introduces EERCASE, a Computer Aided Software Engineering tool that is based on the best practices of the Model Driven Development paradigm to provide a consistent environment for relational database design. EERCASE follows the graphical notation of the Enhanced Entity–Relationship model according to Elmasri and Navathe, implements the EERMM metamodel to avoid syntactically invalid constructs, shows and describes static semantic errors, and generates data definition code that takes into account advanced structural validations. The theoretical and technical framework used for the implementation of EERCASE is discussed, with emphasis on the restrictive and informative validations performed by it. In addition, considering feedbacks on modeling errors and code generation, EERCASE is also presented as a computational environment that favors active learning.